Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Bank Umum Syariah - Rahmadi Siregar (Tsaqila Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine (1) the effect of Capital Adequacy Ratio (CAR) on Return On Assets. (2) the effect of Non-Performing Financing (NPF) on Return On Assets. (3) the effect of Capital Adequacy Ratio (CAR) and Non-Performing Financing (NPF) on Return On Assets.             This research is included in associative research. The population of this study was data on financial statements at Islamic commercial banks from 2015-2020 which were taken on the OJK official website. The purposive sampling was used due to the characteristics of the population that have been known previously by analysing the effect of Capital Adequacy Ratio (CAR), the value of Non-Performing Financing (NPF), and Return on Assets (ROA). To get adequate results, the researchers took steps to analyze monthly data reports. The results of this study indicate that (1) Capital Adequacy Ratio (CAR) has a significant effect on return on assets. (2) Non-Performing Financing (NPF) significantly affects return on assets. (3) Capital Adequacy Ratio (CAR) and Non-Performing Financing (NPF) have a significant effect on return on assets.   Keywords: Capital Adequacy Ratio (CAR) and Non-Performing Financing (NPF), Return On Assets (ROA), Islamic Commercial Banks. Penelitian ini bertujuan untuk mengetahui (1) pengaruh Capital Adequacy Ratio (CAR) terhadap Return On Asset . (2) pengaruh Non Performing Financing (NPF) terhadap Return On Asset. (3) pengaruh Capital Adequacy Ratio (CAR) dan Non Performing Financing (NPF) terhadap Return On Asset. Penelitian ini termasuk dalam penelitian asosiatif. Populasi penelitian ini adalah data laporan keuangan pada bank umum syariah dari tahun 2015-2020 yang diambil pada situs resmi OJK. Penentuan sampel menggunakan metode purposive sampling didasarkan atas ciri-ciri atau sifat-sifat populasi yang sudah diketahui sebelumnya  dengan menggunakan alat analisis pengaruh Capital Adequacy Ratio (CAR), nilai Non Performing Financing (NPF), dan juga return on asset (ROA). untuk mendapatkan hasil yang memadai, maka dari itu peneliti mengambil langkah menganalisis laporan data per bulan. Hasil penelitian ini menunjukkan bahwa (1) Capital Adequacy Ratio (CAR) berpengaruh signifikan terhadap return on asset. (2) Non Performing Financing (NPF)  berpengaruh signifikan terhadap return on asset. (3) Capital Adequacy Ratio (CAR) dan Non Performing Financing (NPF) berpengaruh signifikan terhadap return on asset .   Kata Kunci: Capital Adequacy Ratio (CAR)  dan Non-Performing Financing (NPF), Return On Asset (ROA), Bank Umum Syariah.